Reconfiguration of the radial distribution network using an artificial rabbits optimization approach - Rao, Ganney Poorna Chandra; Krishna, Puvvula Venkata Rama; Rupesh, Mailugundla; Karike, Swathi; Polisetty, Sathyanarayana; Reddy, Sareddy Venkata Rami; Sreedhar, Jadapalli (Institute of Advanced Engineering and Science, 2024)
Lowering system power losses along with improving voltage profile have been major concerns for researchers for the past few decades. The performance of an electrical distribution system (EDS) is dependent on these two factors. This work’s main emphasis is on reconfiguring the radial distribution network (RDN) to diminish system power losses and strengthen the voltage profile. The process of network reconfiguration (NR) involves state transitions of sectionalizing and tie switches while still adhering to the limitations. In this work, the optimal reconfiguration network is determined using the artificial rabbits optimization (ARO) approach. The adopted method is tested using IEEE 119 bus RDN under low, normal, and heavy load conditions. When compared to the current approaches, the adopted methodology produced favorable results.